2008
DOI: 10.1016/j.hrthm.2008.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the diastolic pathway, circuit morphology, and inducibility of human postinfarction ventricular tachycardia from mapping in sinus rhythm

Abstract: Aims-We sought to determine whether sinus rhythm activation maps could be used to detect the origin and characteristics of reentrant ventricular tachycardia in postinfarction patients.Method-In each of 11 post-MI patients, unipolar electrograms were acquired at 256 virtual endocardial sites using non-contact mapping. Electrograms were marked for activation time and mapped on a three-dimensional grid. Spatial differences in sinus-rhythm activation time were correlated to isthmus characteristics, and to activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
(7 reference statements)
1
31
0
Order By: Relevance
“…This early stabilization is consistent with postmortem and animal MRI studies. 17,18 Our finding of multiple VT morphologies showing the same earliest activation site is consistent with Ciaccio et al, 19 who localized the re-entry isthmus in patients with chronic postinfarct VT and found that multiple VT morphologies shared isthmuses in most patients. In chronic postinfarct VT, the median number of inducible arrhythmias was 3, which is consistent with our findings at both time periods.…”
Section: Characteristics Of Vtsupporting
confidence: 90%
“…This early stabilization is consistent with postmortem and animal MRI studies. 17,18 Our finding of multiple VT morphologies showing the same earliest activation site is consistent with Ciaccio et al, 19 who localized the re-entry isthmus in patients with chronic postinfarct VT and found that multiple VT morphologies shared isthmuses in most patients. In chronic postinfarct VT, the median number of inducible arrhythmias was 3, which is consistent with our findings at both time periods.…”
Section: Characteristics Of Vtsupporting
confidence: 90%
“…27 However, fewer fractionated electrogram sites can be detected during sinus rhythm because of, in part, the slower activation rate 19 and because wavefront propagation may sometimes be oriented in the direction thick-to-thin across the LBs, which would not result in a discontinuous wavefront (Figure 1). …”
Section: New Fractionation Modelmentioning
confidence: 99%
“…The NCM has several potential advantages over conventional mapping techniques, in which a 3-dimentional beat-tobeat activation analysis can be performed with a high resolution of >3000 endocardial points, but some concerns have been raised in terms of the reliability of the virtual unipolar electrograms at remote points of >4:0 cm from the center of the MEA, weak resolution capability of the low frequency/amplitude electrograms, and influence of the repolarization on the interpretation of real potentials. However, recent studies have demonstrated the safety and usefulness of the NCM for the mapping and ablation of VT associated with an OMI, 1,2,[10][11][12] in which the NCM was considered useful even in patients with hemodynamically unstable and/or nonsustained VTs. 13) The significance of the DSM for elucidating the low voltage zones is becoming recognized.…”
Section: Discussionmentioning
confidence: 99%